The Normative Evolution of Political Crime in Egyptian Criminal Law 1881 – 1981 - Elkorashy, Anas Sayed (AUC Knowledge Fountain, 2026)
This thesis examines the historical evolution of the Egyptian criminal justice system's approach to managing political opposition. It employs the concept of "political crime" as a heuristic for analyzing the prosecution of dissent, despite the absence of a statutory definition within the legal system. By situating these practices within the broader context of political conflict, the study traces how criminal law has been used to manage rivalry and neutralize perceived threats to the state. Drawing on Fraenkel’s theory of the "Dual State," the thesis argues that modern Egyptian criminal justice has developed through a distinctive dual structure. The research distinguishes the Egyptian experience from the totalitarian context of Fraenkel’s framework. Unlike the trajectory observed in Nazi Germany, the legal duality in Egypt evolved across diverse ideological periods, transitioning from its colonial foundations to the Nasserist revolutionary republic and ultimately Sadat’s era of political and economic liberalization (Infitah). Tracing this trajectory from 1882 to 1981, the study demonstrates how the state of exception became embedded within the legal order. Within this structure, the system operates under a bifurcated logic: maintaining normative legality for routine matters while exercising exceptional power against political dissidents. The thesis reveals that while the ideological contexts of colonialism, Nasserism, and the Sadat era differed significantly, the underlying legal duality has remained a consistent feature. This continuity underscores how the Egyptian state has continually reconfigured its legal mechanisms to maintain control amid shifting political landscapes, demonstrating that this dualism is a foundational aspect of its modern legal history.